Spectrophotometric determination of metronidazole through Schiff’s base system using vanillin and PDAB reagents in pharmaceutical preparations - Siddappa, Kuruba; Mallikarjun, Metre; Reddy, Tukaram; Tambe, Mahesh (Eclética Química, 2008)
Two simple sensitive and reproducible spectrophotometric methods have been developed for the determination of metronidazole either in pure form or in their tablets. The proposed methods are based on the reduction of the nitro group to amino group of the drug. The reduction of metronidazole was carried out with zinc powder and 5 N hydrochloric acid at room temperature in methanol. The resulting amine was then subjected to a condensation reaction with aromatic aldehyde namely, vanillin and p-dimethyl amino benzaldehyde (PDAB) to yield yellow colored Schiff’s bases. The formed Schiff’s bases are quantified spectrophotometrically at their absorption maxima at 422 nm for vanillin and 494 nm for PDAB. Beer’s law was obeyed in the concentration ranges 10 to 65 μg mL-1 and 5 to 40 μg mL-1 with a limit of detection (LOD) of 0.080 μg mL-1 and 0.090 μg mL-1 for vanillin and PDAB, respectively.The mean percentage recoveries were found to be 100.05 ± 0.37 and 99.01 ± 0.76 for the two methods respectively. The proposed methods were successfully applied to determine the metronidazole in their tablet formulations and the results compared favorably to that of reference methods. The proposed methods are recommended for quality control and routine analysis.